Anthropogenic warming reduces the carbon accumulation of Tibetan Plateau peatlands. (1st April 2022) - Liu, Jianbao; Liu, Hanxiang; Chen, Huai; Yu, Zicheng; Piao, Shilong; Smol, John P.; Zhang, Jifeng; Huang, Lingxin; Wang, Tao; Yang, Bao; Zhao, Yan; Chen, Fahu
Abstract: Peatland carbon accumulation generally increased during past intervals of natural warming. With recent anthropogenically-dominated warming being unprecedented over the past ∼2000 years, however, it is unclear how peatland carbon dynamics may operate compared to those under historical natural warmings. Here we examine the impacts of the recent warming from 1850 CE to present (Recent Warm Period; RWP) and the historical warming during 1000–1300 CE (Medieval Warm Period; MWP) on peatland carbon accumulation of the Tibetan Plateau using two continuous peat core records. We observed major seasonal difference between the two warming periods, with growing season (summer) warming dominating the MWP, while greater non-growing season warming characterizing the RWP. Consequently, we found a high net carbon balance during the MWP, suggesting that warming increased plant production more than decomposition of organic matter. In contrast, a low net carbon balance was observed during the RWP because non-growing season warming greatly enhanced soil carbon decomposition that could have completely offset plant carbon uptake. Therefore, recent anthropogenic warming might have induced a different ecosystem response with lower net carbon balance over the past millennium than that during historical natural warmings. As other regions of the globe have similar growing season versus non-growing season warming patterns, the risk of carbon loss from global peatlands may have been underestimated, implying that there is an even greater challenge for managing ecosystem carbon sinks under future climate change. Highlights: Anthropogenic and natural warming had different seasonal warming pattern. Peatland net carbon balance increased during past intervals of natural warming. Anthropogenic warming reduces the net carbon balance. The risk of carbon loss from global peatlands may have been underestimated.